DYNAMICS OF GROWTH AND DEVELOPMENT OF HORSES OF THE KARABAIR BREED - Tleumuratov A. K.; Kaliev B. A. (Zeta Repository, 2023)
This article presents the growth and development of foals of Karabay horses bred in our country, as well as their daily, absolute and relative growth rates.